The war against Ukraine and the EU : facing new realities - Wiesner, Claudia; Knodt, Michèle (2024)
Intro – Contents – List of Contributors – List of Figures – List of Tables – 1 Introduction. The War Against Ukraine: The EU Facing New Realities – Theorising the EU in the New Setting – Impact of the War on the EU as a Polity and its Policies – Ukraine: EU Accession and Perceptions – From Old to New Challenges – References – 2 Back to the Roots? The War in Ukraine and Grand Theories in International Relations – Introduction – Grand Theoretical Debates – Methods – Mapping the Debate – General Features – Main Cause of the War – Stakes – Key Prescriptions for the US/West – Worldviews and Great Debates – Conclusion – References – 3 War and Peace in European Studies: a Zeitenwende? – Introduction – European Studies and War, or, How War Morphed into a Role in Mythology – Why a Zeitenwende Is a No-Go – Previous Wars and EU Studies – The Enduring Consequences of Path-dependencies – A Distinctly Liberal Outlook – War Studies and European Studies – Conclusion and Wider Perspectives – References – 4 Re-ordering the EU and Europe: Old Boundaries and New Challenges – Introduction – The EU, Europe and the World: A Garden Meets a Jungle? – From the 1990s to the 2020s: Key Junctures in the (Re)Ordering of Europe – The Nature and Importance of Boundaries – The EU and the Boundaries of Order in a Changing and Challenging World – Conclusions – References – 5 The War Against Ukraine, the Changing World Order and the Conflict Between Democracy and Autocracy – Introduction – The EU and the Zeitenwende – The Zeitenwende as a Shake-Up of Certainties – The European Union and the Changing World Order – Tackling the New Order: The EU's Reaction – Enhancing Liberal Democracy Externally – Changing Patterns of Liberal Democracy – Liberal Democracy Challenged Internally – Financial Crisis EU